The estimated prevalence of exposure to asthmagens in the Australian workforce - Fritschi, Lin; Crewe, Julie; Darcey, Ellie; Reid, Alison; Glass, D.; Benke, G.; Driscoll, T.; Peters, S.; Si, Si; Abramson, M.; Carey, Renee (BioMed Central Ltd, 2016)
Background: There is very little information available on a national level as to the number of people exposed to specific asthmagens in workplaces. Methods: We conducted a national telephone survey in Australia to investigate the prevalence of current occupational exposure to 277 asthmagens, assembled into 27 groups. Demographic and current job information were obtained. A web-based tool, OccIDEAS, was used to collect job task information and assign exposure to each asthmagen group. Results: In the Australian Workplace Exposure Study – Asthma (AWES- Asthma) we interviewed 4878 participants (2441 male and 2437 female). Exposure to at least one asthmagen was more common among men (47 %) than women (40 %). Extrapolated to the Australian population, approximately 2.8 million men and 1.7 million women were estimated to be exposed. Among men, the most common exposures were bioaerosols (29 %) and metals (27 %), whilst the most common exposures among women were latex (25 %) and industrial cleaning and sterilising agents (20 %). Conclusions: This study provides information about the prevalence of exposure to asthmagens in Australian workplaces which will be useful in setting priorities for control and prevention of occupational asthma.